thrive

answers: 1

Register to add an answer

Answer:

g

x=3 and y=4

hello from mrbilldoesmath!

(7x + 6y) ( 49x^2 - 42xy + 36y^2)

discussion:

in general, the factorization of a^3 + b^3 is

a^3 + b^ 3 = (a + b) ( a^2 - ab + b^2)

in our case note that 343 = 7^3 and 216 = 6^3 so the equation becomes:

343x^3 + 216y^3 = (7x)^3 + (6y)^3

if you think of a (above) as 7x and b as 6y the factorization becomes

343x^3 + 216y^3 =

((7x + 6y) ( (7x)^2 - 7x*6y + (6y)^2) =

(7x + 6y) ( 49x^2 - 42xy + 36y^2)

you,

mrb

(a + b) (a^2 - a b + b^2)

an = 22 + (n-1) *6

110 seats

an=a1+(n-1)(d)

a1 = 22 this is the first item in the sequence

d =6 this is how the sequence goes up

a) an = 22 + (n-1) *6

b) a12 = 22 + (12-1) *6

a12 = 22+11*6

a12 = 22 +88

a12 = 110

315

Anna

For answers need to register.

Contacts

Expert in study